The silence of the spirits - N'Sondé, Wilfried (Global African voices., 2017)
What are the limits of empathy and forgiveness? How can someone with a shameful past find a new path that allows for both healing and reckoning? When Clovis and Christelle find themselves face-to-face on a train heading to the outskirts of Paris, their unexpected encounter propels them on a cathartic journey toward understanding the other, mediated by their respective histories of violence. Clovis, a young undocumented African, struggles with the pain and shame of his brutal childhood, abusive exploits as a child soldier, and road to exile. Christelle, a young French nurse, has her own dark experiences but translates her suffering into an unusual capacity for empathy, forgiveness, and reconciliation. Christelle opens her home and heart to Clovis and presses him to tell his story. But how will she react to that story? Will the telling start Clovis on a path to redemption or alienate him further from French society? Wilfried N'Sondé's brave novel confronts French attitudes toward immigrants, pushes moral imagination to its limits, and constructs a world where the past must be confronted in order to map the future.